PROBLEMATIKA KETERAMPILAN MENULIS DI SDN NGORESAN - Mawarni, Anita Diyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify and analyze various problems faced by first-grade students at SDN Ngoresan in developing their writing skills. The research method used is descriptive qualitative with a case study approach. Data were collected through classroom observations, interviews with teachers, and documentation of students' written work. The findings indicate that the problems related to writing skills among first-grade students include limited fine motor skills, lack of vocabulary, monotonous teaching methods, and insufficient support from both school and home learning environments. The study recommends the use of creative teaching approaches, increased parental involvement, and the strengthening of early literacy culture to overcome these challenges.